Initial hematocrit values after birth and peri/intraventricular hemorrhage in extremely low birth weight infants. (November 2018) - Dekom, Stephanie; Vachhani, Avani; Patel, Krishan; Barton, Lorayne; Ramanathan, Rangasamy; Noori, Shahab
Abstract Objective Ischemia followed by reperfusion plays a significant role in the pathogenesis of peri/intraventricular hemorrhage (P/IVH). Delayed cord clamping promotes placental transfusion to newborn and is associated with decreased P/IVH. We hypothesized that extremely low birth weight (ELBW) infants with higher initial hematocrit (Hct) after birth are less likely to develop P/IVH. Study design Pre- and postnatal data on inborn ELBW infants over 7 years were reviewed. We examined the relationship between P/IVH in the first week and initial Hct using logistic regression modeling. Results We studied 225 infants with a median gestational age (GA) 25.7 (22.4–31.7). Forty-one percent had grade I–IV P/IVH. In univariate analysis, cesarean section (CS) and higher GA, birth weight, 5-minute Apgar, and initial Hct were associated with decreased likelihood of P/IVH while higher maximum PCO2 in first 3 days and use of inotropes/vasopressors, postnatal steroid for hypotension, hypernatremia, transfusion, and use of insulin for hyperglycemia during the first week of life were associated with increased likelihood of P/IVH. In multiple regression analysis, only GA, CS, and initial Hct remained significantly associated with P/IVH. Adjusting for GA and CS, the odds of P/IVH was higher with Hct < 40% (OR 2.04, 95% CI [1.11, 3.76]) and Hct < 45% (2.38 [1.19, 4.76]). Conclusion Higher initial Hct is associated with decreased P/IVH. Initial Hct < 45% was associated with a 2-fold increase in P/IVH. We speculate that lower initial Hct represents a lower intravascular volume status and promotes cerebral hypoperfusion preceding P/IVH.